APPLICATION OF PROJECT-BASED LEARNING MODEL TO IMPROVE STORY WRITING SKILLS OF ELEMENTARY STUDENTS - Uri, Asrila; Notanubun, Zainuddin; Sasabone, Carolina; Salekota, Abu Sale (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This study aims to improve the storytelling skills of fifth-grade students at SD Negeri 2 Poka through the implementation of the Project-Based Learning model. The background of this study is the low writing ability of students, as indicated by an average initial test score of 54.93%, which is below the Minimum Passing Grade. This study used the Classroom Action Research method, which was carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. Data were collected through writing tests, observations, interviews, and documentation, then analyzed descriptively and quantitatively to assess score improvements, as well as descriptively and qualitatively to identify changes in student behavior, motivation, and involvement. The results showed a significant improvement in writing skills, where in cycle I the average student score reached 63.73% with 10 students achieving the KKM, and in cycle II all 15 students (100%) scored above the KKM with an average of 79.66%. This improvement included aspects of determining story titles, vocabulary selection, and overall writing ability. The research findings show that the application of the PjBL model is effective not only in improving writing skills but also in encouraging active participation, developing critical thinking skills, and significantly increasing student motivation to learn.